The impact on pension liabilities of Malaysian government pension scheme from remarriage due to removal of pension clause - Ibrahim R.I.; Siri Z. (American Institute of Physics Inc., 2024)
In the event of death of any government employee, their monthly pension will be given to their widow and their child. The government will stop paying that pension when the widow died and when the widow chooses to remarry. However, in 1st January 2002, the remarriage clause has been removed from the regulations. This would allow all widows who remarried to receive pension as usual. In view of this, there are possibilities that those widows who are still young might remarried. If many of the widows choose to remarry, it will be a burden to the government as it would increase the pension liabilities. However, we do not know how many of the widow will remarry. In view of this, the purpose of the study is to assess the impact to pension liabilities of government pension schemes on individual life due to removal clause of the remarriage by determining the pension factor and to assess to what extent the pension liabilities of government pension schemes would be affected. 2014 AIP Publishing LLC.